Constitution, fundamental rights, artificial intelligence and algorithms - Landa Arroyo, César (2021)
Over the last few decades, the relationship of dependence between humans and technology has been progressive and plausible. This has meant a greater use –by the public and private sector– of technological tools such as artificial intelligence and, in particular, algorithms. These last ones enable the performance of everyday activities such as bank transfers and other more complex ones like the early detection of crimes. In this context, the discussion on whether technological criteria should be the only limits in the development of such advances is increasingly growing.In this article, the author analyzes the influence of artificial intelligence and algorithms in various areas of society, emphasizing the risk that these can generate, in terms of fundamental rights, if its application is not limited by the respect of constitutional rights and principles. Additionally, the author evidences the obligation of the State, within the framework of a democratic and social government model, to regulate practices that, making use of technology, are potential instruments of risk to the rights of individuals.